Anxiety Related to Insomnia Severity Level in Medical Pre-clinic Students of the Faculty of Medicine, Public Health, and Nursing Science (FK-KMK), Universitas Gadjah Mada - Andrian Fajar Kusumadewi; Syifa Nabiel Hadera; Afkar Aulia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Anxiety can cause insomnia or sleep disturbances. Sleep disorders are characterized by abnormal sleep patterns that interfere with daily activities. This study aims to describe the relationship between the incidence rate and the severity of insomnia in medical students in the preclinical phase of the Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada. Methods: This research is an observational study with a cross-sectional design. This research was conducted online and carried out from October 2020 to June 2021. Data collection was carried out for 2 weeks using Jotform as a data retrieval medium. The questionnaire used is generalized anxiety disorder-7 (GAD-7) to measure the level of anxiety and insomnia severity index to evaluate the severity of insomnia. Spearman's Rank analysis test was conducted to determine the correlation between anxiety levels and the severity of insomnia. Results: A total of 130 respondents participated in this study. The majority of respondents are women (71.53%) and are more than 20 years old. Based on Spearman's rank analysis, there was a relationship between anxiety level and insomnia severity (ρ = 0.394), and it was statistically significant with a p-value = 0.000 (p<0.05). Conclusion: There is a relationship between the level of anxiety and the severity of insomnia in medical students in the preclinical phase of FK-KMK Universitas Gadjah Mada.